2017
DOI: 10.1055/s-0036-1597834
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Knife Stereotactic Radiosurgery for Grade 2 Meningiomas

Abstract: This study aims to report long-term clinical outcomes after Gamma Knife radiosurgery (GKRS) for intracranial grade 2 meningiomas. In this Institutional Review Board approved study, we reviewed records of all patients with grade 2 meningiomas treated with GKRS between 1998 and 2014. A total of 97 postoperative histopathologically confirmed grade 2 meningiomas in 75 patients were treated and are included in this study. After a mean follow-up of 41 months, 28 meningiomas had local recurrence (29.79%). Median time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…The prescription dose administered to the lesion also determines the rate of control among meningiomas. Tumours receiving less than doses of 12-13.4 Gy have been reported to display a significantly higher risk of recurrence than tumours receiving higher doses [15,16,[18][19][20]. Our data report a similar observation, with 40% rate of progression among tumours that received less than 12 Gy compared with 16.7% of tumours that received a dose in excess of 12 Gy.…”
Section: Outcomes Of Gkrs In Meningioma and Factors Predicting Poor O...supporting
confidence: 79%
“…The prescription dose administered to the lesion also determines the rate of control among meningiomas. Tumours receiving less than doses of 12-13.4 Gy have been reported to display a significantly higher risk of recurrence than tumours receiving higher doses [15,16,[18][19][20]. Our data report a similar observation, with 40% rate of progression among tumours that received less than 12 Gy compared with 16.7% of tumours that received a dose in excess of 12 Gy.…”
Section: Outcomes Of Gkrs In Meningioma and Factors Predicting Poor O...supporting
confidence: 79%
“…Multiple studies have looked at the use of SRS in WHO grade 2 patients; however there are no prospective trials assessing this treatment modality. One study out of Northwestern University reviewed records of 97 patients with WHO grade 2 meningioma treated postoperatively with Gamma Knife radiosurgery from 1998–2014 [ 24 ]. Three- and 5-year actuarial local control rates were 68.9% and 55.7%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, SRS was applied to 75 grade 2 meningioma cases due to postoperative residual or recurrence. [14] The 5-y OS was determined as 81.1% and the 5-y PFS as 55.7%. In our study, the 5-y PFS was found to be similar to this study with a rate of 57.7%, but no difference was found in terms of OS according to grade.…”
Section: Discussionmentioning
confidence: 99%